SCIENTIFIC APPROACHES OF EASTERN THINKERS IN THE SOCIOLOGICAL STUDY OF SOCIAL PROCESSES OF SOCIETY - Fayzieva Farogat Baxtiyorovna (Web of Journals Publishing, 2023)
The article provides a theoretical justification for various methods of studying public opinion, which first appeared in the East, that practical sociological research in modern sociology are the first manifestations of science related to early society in Central Asia. In addition, the works of Abu Mansur al-Moturidi, Abu Nasr Farabi, Abu Rayhan Beruni, Amir Temur and Alisher Navoi analyzed scientific approaches that make it possible to achieve effective governance by studying social processes in society using special methods that take into account the opinion of the population in society and public administration.
Keywords: sociological research, applied sociological research, social phenomenon, methodology, social groups, scientific cognition, eastern thinkers, public opinion, creativity, art, spirituality, religion and enlightenment, justice, human interests.